ANALISIS TINGKAT LIKUIDITAS PADA PT. AGRO LESTARI, Tbk - R Elfrida Panjaitan (Jurnal Ekonomi dan Bisnis (EK&BI), 2018)
Liquidity is the ability of a company to meet its financial obligations at maturity.Companies that are able to meet their financial obligations when billed. Companies that areable to fulfill their financial obligations in a timely manner shall be declared the company ina liquid state. Liquid means that the company has a means of payment or assets lancer greaterthan the debt lancer or short-term debt. Conversely, if the company can not meet its financialobligations on time, it means the company is in an illiquid state. The level of liquidity of acompany is always influenced by the amount of current assets and current liabilities, therefore,the increase and decrease of items in current assets and current liabilities always affect thelevel of corporate liquidity. The higher the level of corporate liquidity, the greater the guaranteeagainst current liabilities. Conversely, if the level of corporate liquidity is low then the currentdebt can not be guaranteed well at the time of payment settlement. Liquidity ratio is veryimportant that aims to the company can measure the level of the company's ability to meetshort-term obligations that must be met. PT. AGRO LESTARI, Tbk has very good finance, seenfrom the balance sheet of 2012 and 2013 experienced a significant increase between assets andliabilities. Keywords: Analysis, Liquidity